Desalination of seawater using calcined hydrotalcite with different MG/AL ratio / Daiki Tsutsui and Takaaki Wajima - Tsutsui, Daiki; Wajima, Takaaki (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
Salt damaged farmland increases in the world, and a novel method to capture salt in soil for avaiable use of agriculture is desired. In this study, we focused on calcined hydrotalcite as a desalination agent, and desalination properties of calcined hydrotalcite with different Mg/Al ratio from seawater was estimated. Calcined hydrotalcite with Mg/Al ratio of 1 – 6 was prepared, and the desalination ability were investigated using seawater collected from an Imari bay in Saga prefecture, Japan. In comparison, commercial hydrotalcite was done as the same procedure. As a resalt, the decrease of salinity was confirmed using all calcined hydrotalcites and the decreasing rates were almost same. The calcined hydrotalcite with approximately Mg/Al = 3.0 indicated the highest desalination property, due to the decrease of Na+ , Mg2+, Cl- and SO4 2- with addition of calcined hydrotalcite. The structure of calcined hydrotalcite returned to that of hydrotalcite by reconstruction reaction